Down-Regulation of miR-378d Increased Rab10 Expression to Help Clearance of Mycobacterium tuberculosis in Macrophages - Zhu, Yifan; Xiao, Yao; Kong, Delai; Liu, Han; Chen, Xi; Chen, Yingyu; Zhu, Tingting; Peng, Yongchong; Zhai, Wenjun; Hu, Changmin; Chen, Huanchun; Suo Lang, Si Zhu; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (M. tb) can survive in the hostile microenvironment of cells by escaping host surveillance, but the molecular mechanisms are far from being fully understood. MicroRNAs might be involved in regulation of this intracellular process. By RNAseq of M. tb-infected PMA-differentiated THP-1 macrophages, we previously discovered down-regulation of miR-378d during M. tb infection. This study aimed to investigate the roles of miR-378d in M. tb infection of THP-1 cells by using a miR-378d mimic and inhibitor. First, M. tb infection was confirmed to decrease miR-378d expression in THP-1 and Raw 264.7 macrophages. Then, it was demonstrated that miR-378d mimic promoted, while its inhibitor decreased, M. tb survival in THP-1 cells. Further, the miR-378d mimic suppressed, while its inhibitor enhanced the protein production of IL-1β, TNF-α, IL-6, and Rab10 expression. By using siRNA of Rab10 (siRab10) to knock-down the Rab10 gene in THP-1 with or without miR-378d inhibitor transfection, Rab10 was determined to be a miR-378d target during M. tb infection. In addition, a dual luciferase reporter assay with the Rab10 wild-type sequence and mutant for miR-378d binding sites confirmed Rab10 as the target of miR-378d associated with M. tb infection. The involvement of four signal pathways NF-κB, P38, JNK, and ERK in miR-378d regulation was determined by detecting the effect of their respective inhibitors on miR-378d expression, and miR-378d inhibitor on activation of these four signal pathways. As a result, activation of the NF-κB signaling pathway was associated with the down-regulation of miR-378d. In conclusion, during M. tb infection of macrophages, miR-378d was down-regulated and functioned on decreasing M. tb intracellular survival by targeting Rab10 and the process was regulated by activation of the NF-κB and induction of pro-inflammatory cytokines IL-1β, TNF-α, IL-6. These findings shed light on further understanding the defense mechanisms in macrophages against M. tb infection.